The Application of Mechanical-Chemical Corrosion Theory in Downhole Tubing CO2 Corrosion Research - Peike Zhu; Wei Yan; Liyu Deng; Jingen Deng (Advances in Materials Science and Engineering)
Indoor simulating experiment is a main method for oil field CO2 corrosion research. Experimental parameters are very important for an accurate simulation. Based on the mechanical-chemical corrosion theory, the external load may be possible to accelerate the corrosion rate. However, the influence of N2 pressure on CO2 corrosion during the simulating experiment is negligible. Because the coupon stress induced by additional N2 pressure is very low, therefore, the N2 adding procedure can be cancelled and a more safety working space for researchers will be created. However, it does not mean that mechanical-chemical corrosion influence can be ignored. For downhole tubing, the hoop stress generated from the formation compress or liquid column internal pressure is remarkable; stress effect on corrosion has to be taken into consideration. When pit cavity especially occurred on the internal tubing surface, the stress concentration effect will induce a much higher local stress. Mechanical-chemical corrosion will become significant and more study should be performed on this topic.